THE EFFECT OF GIVING LAMTORO LEAF JUICE (Leucaena leucocephala) THROUGH DRINKING WATER ON THE CARCASS OF MALE BALINESE DUCKS - N.N., Mira; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aims to determine the effect of giving lamtoro leaf juice through drinking water on the carcass cracks of male balinese ducks. This study was carried out for 8 weeks. The design used in this study was a complete randomized design (RAL) with 4 treatments and 4 repeats, so it consisted of 16 experiments. Each experimental unit used 3 male balinese ducks. The treatment given to male balinese ducks in the form of lamtoro leaf juice in drinking water is: (P0) drinking water without lamtoro leaf juice, (P1) drinking water with 2% lamtoro leaf 385 juice, (P2) drinking water with 4% lamtoro leaf juice, and (P3) drinking water with 6% lamtoro leaf juice. The variables observed were cutting weight, carcass weight, carcass percentage, and carcass fracture percentage which includes chest, upper thighs, lower thighs, wings, and back. The results showed that giving lamtoro leaf juice in drinking water 2%, 4% and 6% had no real effect (P>0.05) on carcass weight, carcass percentage, and carcass fracture percentage. Based on the results of the study, it can be concluded that giving lamtoro leaf juice to drinking water 2%, 4% and 6% has not been able to increase the of carcass weight, carcass percentage and carcass cracks.